Fumaça cirúrgica: percepções da equipe intraoperatória à luz da teoria cultural do risco - Peserico, Anahlú (2024)
Objective: The purpose of this study is to know the perception of risk about exposure to surgical smoke among workers of the intraoperative team, in the light of the Cultural Theory of Risk. Method: Therefore, a qualitative, exploratory, and descriptive study will be carried out in the light of the aforementioned theory, seeking to deepen the theme. The scenarios chosen for the investigation were the Surgical Center Units of the two hospitals-schools, linked to public universities with participation in the practice of teaching, research and extension, integrated into the Unified Health System. The population will be composed of 53 workers of the intraoperative team, namely anesthesiology and surgery preceptors, anesthesiology and surgery residents, nurses, nursing technicians, and surgical instrumentologists. Data will be collected through individual and collective semi-structured interview and non-participant observation, and analyzed using thematic content analysis with the help of the theoretical framework of the Cultural Theory and the functional analysis of the grid-group typology. This research will meet the ethical precepts established in Resolution 466/12 of the National Health Council and will be submitted to the Research Ethics Committee from both institutions. Results: the results were presented and discussed through two thematic categories, each of them organized into two subcategories, namely: the first “Surgical smoke in the light of the critical approach of the cultural theory of risk” deals with the incipient knowledge about the surgical smoke, the dialectic between reality and utopia, rationality and uncertainty that generate the risk perceptions of intraoperative workers. The second “The social construction of the risk of surgical smoke through the functional analysis of the grid-group typology”, maps the cultural prejudices and the pattern of interpersonal relationships in this social unit, revealing how the selection and prioritization of the risk of surgical smoke operates, highlighting the dominant way of life of this group. The results of the study support that intraoperative workers have limited knowledge about the subject of surgical smoke, both regarding signs and symptoms and appropriate prevention/protection measures for this type of exposure. This reveals a low perception of risk, surgical smoke is characterized as an invisible risk. Cultural prejudices are based on a unique belief system and the devaluation of risk; the social relationships constructed support preferences such as self-orientation, autonomy and freedom in negotiations, without restrictions that disturb benefits and rewards in your care practice. The collective construct of this group designs its own risk portfolio, in which surgical smoke does not gain space. In this case, the perception of risk is more aligned with an individualistic worldview. It is concluded that the cultural theory of risk was an appropriate heuristic for understanding the risk perception of this group. Conclusion: incipient knowledge about the occupational risk of surgical smoke and the absence and/or non-adherence to appropriate protection/prevention measures for this type of exposure can lead to health problems for exposed workers in the short and long term. Thus, the social relationships constructed support a thought strongly rooted in positivism. Therefore, the collective construct of this group designs its own risk portfolio, in which surgical smoke does not deserve prominence in the debate on risks in the surgical environment. In this social unit, a culture is assumed in which the dominant perception of risk is more aligned with an individualistic worldview.